Performance and usability evaluation of three LDH-based malaria rapid diagnostic tests in Kédougou, Senegal - Babacar Souleymane Sambe; Stephanie Zobrist; William Sheahan; Divya Soni; Aissatou Diagne; Ibrahima Sarr; Arona Sabene Diatta; Serigne Ousmane Mbacke Diaw; Allison Golden; Hannah Slater; Ihn Kyung Jang; Nerie Roa; et al. (Parasites & Vectors)
Abstract Background The emergence of Plasmodium falciparum (Pf) parasites with deleted histidine-rich protein 2 and 3 (hrp2/hrp3) genes threatens the performance of HRP2-based malaria rapid diagnostic tests (RDTs). RDTs targeting Pf lactate dehydrogenase (LDH) may address current product limitations and improve case management. The objective of this study was to evaluate the performance and usability of three LDH-based RDTs in febrile patients. Methods A cross-sectional diagnostic accuracy study was conducted in Kédougou, Senegal. Capillary blood was tested using the SD BIOLINE Ag Pf RDT (Abbott Diagnostics Korea Inc., Republic of Korea) and three LDH-based RDTs (BIOCREDIT Malaria Ag Pf [pLDH], BIOCREDIT Pf [pLDH/HRPII] and BIOCREDIT Pf/Pv [pLDH/pLDH]; Rapigen Inc., Republic of Korea). Venous blood was collected and used to repeat the BIOCREDIT RDTs and conduct microscopy. Frozen venous specimens were tested using a reference PCR assay. A quantitative multiplex malaria antigen assay measured antigen concentration. RDT performance was determined and analyzed as a function of antigen concentration distribution. Usability of the Pf-only BIOCREDIT tests was evaluated using a questionnaire. Results Of the 220 participants, 154 (70%) were Pf-positive by PCR. The Pf (pLDH/HRPII) test demonstrated the highest sensitivity at 78% (95% confidence interval [CI] 70.9–84.5%); specificity was 89% (95% CI 79.4–95.6%). All RDTs performed better than microscopy (53% sensitivity). Although the HRP2 line on the Pf (pLDH/HRPII) test was more sensitive than the SD BIOLINE HRP2-based test (71%, 95% CI 63.6–78.4%), the sensitivities of the PfLDH lines alone on all three BIOCREDIT tests (61–64%) were lower than that of the SD BIOLINE HRP2 test. RDTs performed better when compared to antigen concentration over PCR results. Improved sensitivity of the Pf (pLDH/HRPII) test was driven by the HRP2 line. Line intensity correlated with antigen concentration. Predicted sensitivity using the analytical limit of detection (LOD) was comparable to the observed sensitivity. RDTs demonstrated acceptable usability. Conclusions Both HRP2 and LDH contributed to the sensitivity of the best-performing Pf-RDT. In populations such as this with low rates of hrp2/hrp3 deletions, the PfLDH line alone cannot compensate for the performance of the HRP2 line, even with the improved PfLDH LOD of the BIOCREDIT tests. RDT analytical LODs can be used to predict performance in populations with known antigen concentrations. Graphical Abstract